Evidence-Based Practice in the United States: Challenges, Progress, and Future Directions. Issue 1 (2nd January 2016) - Correa-de-Araujo, Rosaly
ABSTRACT: Scientific literature demonstrates that advances in evidence-based nursing have improved systems of care and women's health outcomes. Experts agree that nurses worldwide can play a key role in building such evidence and working with interdisciplinary health care teams and systems to accelerate its implementation.